Analisis Fundamental Keputusan Investasi Saham Berdasarkan Earning Per Share (EPS) - Anisya Sukmawati; Julio Adrianus Sutanto (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Fundamental analysis is the analysis based on the economic fundamentals of the company, to look at the long-term prospects of the company. The investment was done to be able to maintain the value of the wealth in the future. In investing, an investor would certainly expect great benefits in the future. Earning Per Share (EPS) is one of the indicators, the calculation of the ratio of a stock investment decisions to take in this research, can be seen on the company's profit/loss report. The object of this study is a SOE company engaged in air transportation PT. Garuda Indonesia Tbk, represents the best airline in Indonesia and has been recognized by the world. The purpose of this study is to provide an investment decision consideration stock against these companies, by looking at the fundamental side of the company. The result of this research, the company's stock hasn`t been in good shape to be invested if seen from the Earning Per Share (EPS) of the company. However, viewed from the side of performance, achievement, and public confidence towards the company need to be consideration for investors before stock investment decisions.